Securing Europe's future: Strengthening ICT competitiveness for economic and national security - Fredrik Erixon; Oscar Guinea; Dyuti Pandya (European Centre for International Political Economy (ECIPE), 2024)
Europe's Information and Communication Technology (ICT) sector, including ICT manufacturing such as telecom equipment and electronic components, as well as ICT services such as software, telecommunication services, and data processing, is no longer merely an economic pillar but a strategic asset essential for national security and defence capabilities. This paper identifies two concerns linking technology and national security: the exploitation of ICT as a gateway to critical infrastructure and the weaponisation of trade and technological dependencies in ICT by foreign nations. Addressing these two challenges requires tailored approaches, as they involve distinct nations and contexts.
Keywords: 330